2015
DOI: 10.1111/exd.12854
|View full text |Cite
|
Sign up to set email alerts
|

The role of aldo‐keto reductase 1C3 (AKR1C3)‐mediated prostaglandin D2 (PGD2) metabolism in keloids

Abstract: Keloids are progressively expanding scars, mostly prevalent in individuals of African descent. Previous data identified increased mast cell number and activation state in keloids suggesting a role in disease progression. The major eicosanoid secreted by mast cells is prostaglandin D2 (PGD2), a relatively unstable pro-inflammatory mediator which can be spontaneously converted to 15-deoxy-(Delta12,14)-prostaglandin J2(15d-PGJ2) or enzymatically metabolized to 9α,11β-PGF2 by aldo-keto reductase 1C3 (AKR1C3). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Previous studies found increased levels of ROS in keloids and proposed their implication in the pathogenesis of keloids [17]. Evidence of ROS accumulation supports the hypothesis that oxidative stress is a mechanism of cellular proapoptotic actions in keloid cells [18].…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies found increased levels of ROS in keloids and proposed their implication in the pathogenesis of keloids [17]. Evidence of ROS accumulation supports the hypothesis that oxidative stress is a mechanism of cellular proapoptotic actions in keloid cells [18].…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, 15d-PGJ 2 was found to inhibit a series of fibroblast-associated processes, such as TGF-β stimulation of collagen gene expression, transdifferentiation of myofibroblasts (30) as well as the Smad-dependent promoter activity (31). 15d-PGJ 2 has also been shown to attenuate the proliferation of keloid cells, inhibit collagen gel contraction as well as to increase cleavage of caspase-3 (32). It has been demonstrated, however, that 15d-PGJ 2 and a prostanoid DP2 receptor agonist (13,14-dihydro-15-keto-prostaglandin D2) had no clear effect on the scratching behavior of rodents, thus suggesting that such prostaglandin D2 suppressive effect ought to be mediated by the prostanoid DP1 receptor instead (33).…”
Section: Discussionmentioning
confidence: 99%
“…PGD2 is a relatively unstable lipid with a half-life of approximately 30 min in plasma and can be metabolized to other types, including PGF2α, 9α,11β-PGF2 and the J series of PGs (such as PGJ2, Δ12-PGJ2, and 15d-PGJ2) [ 13 ]. Moreover, 15d-PGJ2, a natural ligand that activates peroxisome proliferator-activated receptor (PPAR-γ), inhibits the NF-κB pathway and induces oxidative stress, is an important lipid participating in various biological and pathological conditions [ 56 , 57 ]. A stereoisomer of PGF2α, 9α,11β-PGF2, which is metabolized from PGD2 by the enzyme PGD 11-ketoreductase, has been shown to mediate various biological activities, such as the contraction of bronchial smooth muscle cells, inhibition of platelet aggregation and induction of chemoattraction of various immune cells [ 56 ].…”
Section: Prostaglandinsmentioning
confidence: 99%
“…An increasing body of in vivo or in vitro evidence has shown that 15d-PGJ2 possesses antifibrotic properties in various experimental models, most of which occur in a PPAR-γ-independent manner. Alon et al showed that 15d-PGJ2 in keloids attenuates keloid cell proliferation, inhibits collagen gel contraction, and increases cell apoptosis by inducing oxidative stress in vitro [ 56 ]. AKR1C3 is an enzyme that metabolizes PGD2 to 9α,11 β-PGF2, the inhibition of which increases the concentration of 15d-PGJ2 and is a potential treatment for skin keloids [ 56 ].…”
Section: Prostaglandinsmentioning
confidence: 99%
See 1 more Smart Citation